1981
DOI: 10.1007/bf00258470
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence assays and pharmacokinetic studies of 4′-deoxydoxorubicin and doxorubicin in organs of mice bearing solid tumors

Abstract: The pharmacokinetic of 4'-deoxydoxorubicin, a new analog of doxorubicin, was compared with that of its parent compound in mice treated with equal and equiactive doses. The levels of total fluorescence due to the initial drugs and to metabolites were determined in tissue extracts by fluorometry. 4'-Deoxydoxorubicin reached the same tissue levels as doxorubicin in all the organs tested except in spleen and lung, where a higher peak was found in the animals treated with the new analog. The rate of elimination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…This analogue reached the same tissue levels as Dx in all organs tested except spleen and lung where comparatively higher peaks were detected (9). In the neoplastic tissue the analogue reached higher concentrations than Dx, as shown by a comparison of the areas under the curve, up to 72 h following administration, and this finding may be correlated with its higher potency.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…This analogue reached the same tissue levels as Dx in all organs tested except spleen and lung where comparatively higher peaks were detected (9). In the neoplastic tissue the analogue reached higher concentrations than Dx, as shown by a comparison of the areas under the curve, up to 72 h following administration, and this finding may be correlated with its higher potency.…”
Section: Introductionsupporting
confidence: 52%
“…In general, dxDx appears to be eliminated more rapidly than Dx. The faster clearance from the heart has been advocated as one of the reasons for the lower cardiotoxicity of the new analogue (9).…”
Section: Introductionmentioning
confidence: 99%
“…A pharmacokinetic study in the mouse indicated that equal doses of doxorubicin or esorubicin achieved equivalent drug levels in all organs, except the lung and the spleen where higher concentrations were observed with esorubicin (12). Faster elimination from normal tissues, including the heart, and larger area under the concentration versus time curve in the tumor were consistent with higher potency and the lower cardiotoxicity of the new analog (12).…”
Section: Introductionmentioning
confidence: 68%
“…Faster elimination from normal tissues, including the heart, and larger area under the concentration versus time curve in the tumor were consistent with higher potency and the lower cardiotoxicity of the new analog (12). This study was undertaken to determine the pharmacokinetic behavior of esorubicin in man.…”
Section: Introductionmentioning
confidence: 99%
“…DXDX is active against several ex perimental tumors and human tumors transplanted into nude mice [4. 5] and DXDX showed efficacy both in vivo and in vitro also in neoplasms resistant to doxorubicin [6][7][8], Phase I trials have established gra nulocytopenia as limiting toxicity and several studies suggest a lower cardioloxicily of DXDX in com parison with doxorubicin [9][10][11]. Moreover, other nonhematologic side effects (alopecia and gastrointes tinal toxicity, in particular) appeared to be less pro nounced than those induced by the parent compound [ …”
Section: Introductionmentioning
confidence: 99%